GEOSTRATEGY OF BITUNG PORT AREA ON INDONESIA'S MARITIME SECURITY PERSPECTIVE (STUDY ON THE INDO-PACIFIC REGION IN 2018-2019) - Supartono, Supartono; Purwanto, Purwanto; Nugraha, M. Harry Riana (Jurnal Pertahanan & Bela Negara, 2020)
The Port of Bitung area has a number of potentials that can impact the structure of national security and national defense, because it has a strategic concept for the Indo-Pacific Region. The Bitung Port area as an international hub port, stated in the Minister of Transportation Decree Number 54 of 2002 concerning the Implementation of Sea Ports. The method in this study used a qualitative descriptive approach and data analysis techniques used an interactive of model analysis. This study analyzes the Geostrategy concept for the Port of Bitung Region as part of a national security strategy to strengthen national defense based on the maritime security side and the economic implications of the Indo-Pacific Region. The results show that in general the analysis of the strategy of the Bitung port area in maritime security studies for national national security and national defense shows several things: 1) the strategic conditions of the Bitung Port area need to be supported by strategic and integrated policies between the Central government and the North Sulawesi Province Bitung City; 2) the development of special economic zones (KEK) requires accelerated implementation of policies in a sustainable manner with full support from the budget side, this is to strengthen the territorial basis in the geostrategic concept; and 3) there needs to be an approach towards the community in supporting the realization of the strategic area of Bitung City, North Sulawesi. The fulfillment of these requirements has made the Bitung Port area capable of supporting geostrategy through strategic maritime security studies and economic implications, because it is located in the Indo-Pacific Region as a center for political and economic defense so as to strengthen national security and national defense.Keywords: geostrategy, port area, Bitung Harbor, Indo-Pacific region